Analysis of Outcome Domains in Adult Cochlear Implantation: A Systematic Review. (August 2016) - Vila, Peter M.; Hullar, Timothy E.; Buchman, Craig A.; Lieu, Judith E. C.
Objectives: To determine the breadth of outcome domains used in the reporting of adult cochlear implant surgery for the purpose of registry and quality measure development. Data Sources: Systematic review of randomized controlled trials. Review Methods: In consultation with a medical librarian, search strategies were constructed to identify randomized controlled trials studying adults undergoing cochlear implantation. MEDLINE, EMBASE, Scopus, CINAHL, Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials, and the Database of Abstracts of Reviews of Effects were searched from database inception to July 2015. Studies were evaluated for level of evidence and risk of bias with the Cochrane Collaboration's Risk of Bias Tool, and outcome domains were extracted from each study. Results: Of 4473 unique citations found, 8 studies were included in this review. All 8 trials were evidence level 1B. Risk of bias was low in 2 trials and high in the other 6. Reported outcome domains included speech perception in quiet and noise, speech tracking, quality of life, timbre perception, hearing preservation, vestibular function, electrode insertion technique, functional measures, functional imaging, fitting time, and tinnitus. Conclusions: An analysis of randomized controlled trials studying cochlear implantation in adults yielded a wide spectrum of outcome domains. This is the first study to comprehensively describe the breadth of outcome domains in adult cochlear implantation. Validated instruments from these domains could be considered for potential inclusion as quality measures and registry use.